2019
DOI: 10.1186/s12862-019-1409-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the coding sequences of clownfish reveals molecular convergence in the evolution of lifespan

Abstract: Background Standard evolutionary theories of aging postulate that reduced extrinsic mortality leads to evolution of longevity. Clownfishes of the genus Amphiprion live in a symbiotic relationship with sea anemones that provide protection from predators. We performed a survey and identified at least two species with a lifespan of over 20 years. Given their small size and ease of captive reproduction, clownfish lend themselves as experimental models of exceptional longevity. To identify genetic corr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 84 publications
(98 reference statements)
2
22
0
Order By: Relevance
“…In this association, the benefits for the anemonefish include protection from predators , removal of external parasites , gaining additional nutrients from tentacles, and increase in reproductive fitness through egg protection Saenz-Agudelo et al 2011). Anemonefish are long-lived, and are used as an experimental model of exceptional longevity Sahm et al 2019). Their lifespan is generally more than 30 years.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…In this association, the benefits for the anemonefish include protection from predators , removal of external parasites , gaining additional nutrients from tentacles, and increase in reproductive fitness through egg protection Saenz-Agudelo et al 2011). Anemonefish are long-lived, and are used as an experimental model of exceptional longevity Sahm et al 2019). Their lifespan is generally more than 30 years.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…aridity) strictly limits the natural lifespan of Nothobranchius fishes in the wild (Tozzini et al, 2013), this short lifespan is retained under captive conditions and is coupled to rapid expression of a host of conserved age-associated phenotypes (Cellerino et al, 2016). In addition, the genus Nothobranchius evolved from a non-annual (therefore, longerlived) ancestor, the sister genus Aphyosemion (Sahm et al, 2019) and the two taxa provide a sharp phenotypic contrast.…”
Section: Introductionmentioning
confidence: 99%
“…The lifespan of A. percula has been estimated to be about 30 years [34]. Sahm and collaborators (2019) performed a survey of anemonefish lifespan data in the wild and in captivity, in which they identified at least two additional species (A. ocellaris and A. melanopus) with a lifespan of over 20 years [35]. Because this lifespan is longer than other teleost fish of the same size, anemonefish could become an experimental model for long-lived vertebrates [34].…”
Section: Life Spanmentioning
confidence: 99%
“…Because this lifespan is longer than other teleost fish of the same size, anemonefish could become an experimental model for long-lived vertebrates [34]. For example, recently, anemonefish have been used to understand the genetic architecture underlying differences in lifespan [35]. Taking advantages of the transcriptome of 5 anemonefish species, Sahm et al (2019) identified genes that underwent accelerated molecular evolution in association with the evolution of a long lifespan [35].…”
Section: Life Spanmentioning
confidence: 99%